Pengaruh Rotasi Kerja dan Beban Kerja terhadap Kinerja Karyawan Hotel Truntum Padang - Dini Putri Ayu; Yuke Permata Lisna; Youmil Abrian (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2025)
This research was conducted because there is a phenomenon that causes employee performance to decline at the Truntum Padang Hotel. The aim of this research is to explain how job rotation and workload affect employee performance. This research was conducted using quantitative descriptive methods with associative causal relationships. The research location is the Truntum Padang Hotel. The non-probability sampling type is used for purposive sampling. The data used in this research is primary data. The questionnaire created based on the Likert scale has been processed before passing the validity and reliability test process using SPSS 26.00. This research found that job rotation is an important factor in improving employee performance at the Truntum Padang Hotel. and workload have a significant influence on employee performance at the Truntum Padang Hotel. The research results show that the work rotation (X1) and workload (X2) variables are both rated very well based on statistical calculations, with average TCR values ​​of 4.36% and 4.26% respectively. employee performance (Y) is also considered very good with an average TCR value of 4.34%.